The role of vitamin D in the prevention and treatment of autoimmune diseases – A literature review and analysis of research - Zawół, Monika; Zimonczyk, Mariusz; Pawlik, Wiktoria; Nojek, Paweł; Nowotarska, Agnieszka; Błaszczyński, Gustaw (Journal of Education, Health and Sport, 2024)
Introduction and purpose. Autoimmune diseases are a group of diseases in which the immune system attacks the body’s own cells, leading to chronic inflammation and tissue damage. In the pathogenesis of these diseases, dysregulation of the immune response, including excessive activity of T and B lymphocytes and macrophages, play a key role. The aim of this work is to review the role of vitamin D in the prevention and treatment of autoimmune diseases, with particular emphasis on Hashimoto’s disease, rheumatoid arthritis and Crohn’s disease. Methods. A literature review was conducted based on the PubMed and Google Scholar databases, using the key words: "vitamin D", "Hashimoto’s disease", "rheumatoid arthritis", "Crohn’s disease". Articles published within the last five years were prioritized. Brief description of the state of knowledge. Vitamin D affects the immune system through the presence of vitamin D receptors (VDR) on immune cells, such as T and B lymphocytes and macrophages. The active form of vitamin D (calcitriol) supports the development of regulatory T cells (Treg), which inhibit excessive inflammatory response, and reduces the activity of Th1 and Th17 lymphocytes. Vitamin D deficiency can disrupt this regulation, increasing the risk of developing autoimmune diseases. Conclusions. Vitamin D plays an important role in the prevention and treatment of autoimmune diseases. It has an immunomodulatory effect, restoring the balance of the inflammatory response, which is crucial in the treatment of diseases such as Hashimoto’s, rheumatoid arthritis and Crohn’s disease. Vitamin D supplementation can alleviate symptoms, improve organ function and reduce the severity of autoimmune diseases.